2015
DOI: 10.17221/113/2015-swr
|View full text |Cite
|
Sign up to set email alerts
|

Comparing different data preprocessing methods for monitoring soil heavy metals based on soil spectral features

Abstract: Gholizadeh A., Borůvka L., Saberioon M.M., Kozák J., Vašát R., Němeček K. (2015): Comparing different data preprocessing methods for monitoring soil heavy metals based on soil spectral features. Soil & Water Res., 10: 218-227.The lands near mining industries in the Czech Republic are subjected to soil pollution with heavy metals. Excessive heavy metal concentrations in soils not only dramatically impact the soil quality, but also due to their persistent nature and indefinite biological half-lives, potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(81 citation statements)
references
References 40 publications
(56 reference statements)
5
65
0
Order By: Relevance
“…Spectra preprocessing algorithms entailed a range of mathematical techniques for refining light scattering in spectral reflectance measurements and data improvement before the data were used in calibration models. The first derivative transformation, which was utilized in this study, is very efficient for eliminating baseline offset and, according to some researchers, gives the best results and uppermost accuracy among other algorithms [28,41,53]. In this study, before all further spectra treatments, the noisy parts of the spectra, ranges 350-399 nm and 2450-2500 nm, were removed, and the spectra were subjected to Savitzky-Golay smoothing with a second-order polynomial fit and 11 smoothing points [18,54] for eliminating the artificial noise caused by the spectroradiometer device.…”
Section: Spectra Preprocessingmentioning
confidence: 98%
See 2 more Smart Citations
“…Spectra preprocessing algorithms entailed a range of mathematical techniques for refining light scattering in spectral reflectance measurements and data improvement before the data were used in calibration models. The first derivative transformation, which was utilized in this study, is very efficient for eliminating baseline offset and, according to some researchers, gives the best results and uppermost accuracy among other algorithms [28,41,53]. In this study, before all further spectra treatments, the noisy parts of the spectra, ranges 350-399 nm and 2450-2500 nm, were removed, and the spectra were subjected to Savitzky-Golay smoothing with a second-order polynomial fit and 11 smoothing points [18,54] for eliminating the artificial noise caused by the spectroradiometer device.…”
Section: Spectra Preprocessingmentioning
confidence: 98%
“…The question arises: why another study on different calibration approaches? As shown by Gholizadeh et al [10,41], choosing the most robust calibration technique can help to achieve a more reliable and accurate prediction model. Moreover, different studies reveal different results, because the nature of the target function has a significant effect on the performance of the different prediction approaches.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Suitable data preprocessing, calibration and validation strategies, which frequently differ for users and operators, to calibrate soil prediction models, influence the final model too. For example, Gholizadeh et al [14] indicated that the 1st derivative preprocessing method gave the best prediction of heavy metals in the Czech Republic mining areas, in comparison to 2nd derivative, multiplicative scatter correction (MSC), standard normal variate (SNV) and continuum removal (CR). Viscarra Rossel and Behrens [15] and Araujo et al [16] applied partial least square regression (PLSR), boosted regression trees (BRT) and support vector machine regression (SVMR) methods for the prediction of clay; SVMR offered the most successful prediction model due to its ability to solve the multivariate calibration problems and to reduce problems with heterogeneity and non-linearity.…”
Section: Introductionmentioning
confidence: 99%
“…The transport of heavy metals in soil is the result of processes between soil and metal components, which include processes of physical, chemical, and biological nature (Violante et al 2008). However, soil is not only a passive acceptor of heavy metals, polluted soils become a source of contamination for other environmental components and the food chain (Gholizadeh et al 2015). In addition, heavy metals are non-degradable and persistent, their presence in soil is stable and doi: 10.17221/107/2016-SWR long-term (Lizárraga-Mendiola et al 2009).…”
mentioning
confidence: 99%